The Role of Local Wisdom Values for Achieving Healthy Housing Concept in Humid Tropical Climate - Pramitasari, Putri Herlia; Harjanto, Suryo Tri (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
Indonesia has a variety of vernacular architecture. The various of local wisdom values from Indonesian traditional houses have succeeded for local identity strengthening. On the other hand, residential housing currently prioritizes functional needs only, while aspects of formal characteristics and local wisdom values are not the main considerations in the design of today's residential housings. The role and characteristics of local wisdom values as an approach in residential design is certainly interesting to study more deeply. Descriptive analysis research method through field observation and literature study which was carried out as an effort to answer the research problem. The results show that the optimization of the passive design strategy of residential buildings by adapting local wisdom values is expected to increase indoor thermal comfort levels, achieve building energy efficiency, strengthen the urban identity, preserve architectural styles, also develop of sustainable architecture. In this way, healthy housing with local character can be realized throughout Indonesia.